A comprehensive rubric for instructional design in e-learning. Issue 2 (5th March 2018) - Debattista, Martin
Abstract : Purpose: The recognition of practice in online instruction is still subject to interpretation and different approaches as a result of the rapid changes in technology and its effect on society. The purpose of this paper is to address these differences through a synthesis that can be easily accessed and consulted by educators in the field of e-learning. Design/methodology/approach: This paper reviews different examples of rubrics and instruments in higher education to propose a more comprehensive rubric that constitutes a synthesis of how some institutions in HE approach best practice in this field. Findings: The proposed comprehensive rubric emanating from the synthesis of different approaches supports the development, remixing, sharing and integration of online modules and courses by providing a single reference point with as wide a range as possible of potential pedagogical tools, facilities and approaches to e-learning. Research limitations/implications: It is not within the scope of this paper to review quality assurance processes and administrative components, but to propose a rubric for course design and self-review of faculty and higher education institutions for a better alignment with what is regarded as current standard best practice. Practical implications: Instructional designers in e-learning have a new comprehensive rubric that can consult at design stage. Originality/value: Different approaches towards what is called "good practice" are brought together and analysed to provide a synthesis and a single source that can be consulted by practitioners in the field of e-learning.